Hégésippe chez Eusèbe Histoire Ecclésiastique, IV, 21-22 : Diadochḗ et origine des hérésies - Antonelli, Cecilia 1984- (2011)
The present contribution submits to investigation the main themes of Hegesippus’ Greek fragments quoted by Eusebius of Caesarea, Ecclesiastical History IV, 21-22 ; our analysis takes account as well of the other fragments of the same author, of their historical context and of the previous studies about the author and the subjects mentioned and pays also attention to distinguish the original message of Hegesippus’work from the interpretation given to it by Eusebius for his own narrative and ideological aims. We so tried to offer some new results about some debated problems : Hegesippus’oriental origin and his proposed, but improbable, Jewish birth ; the nature and aim of his work, called Hypomnèmata, probably some « annotations » of heresiological and apologetical subject ; his activity in the context of the constitution of the first lists of bishops in ancient Christian communities, at the time of the rising of Christian « heresies » and of the first identification of some so-called « apocryphal » writings, in the second half of the 2nd century. Some particular points have been studied: a possible connection between Hegesippus’work and Clement of Rome’s Letter to the Corinthians ; the nature and meaning of the διαδοχή Hegesippus would have composed travelling through Corinth to Rome ; his use of Ancient Testament testimonia as a foreshadowing of the origin of heresies ; his knowledge of some « apocryphas » and some Judæo-Christian writings, such as the Gospel of the Nazareans and the « Syriac Gospel ».
Keywords: Eusebius -- Caesariensis -- 260-339; Neutestamentliche Apokryphen